Atomic energy in India, its contribution towards self-reliance in science and technology ; and, Safety aspects of nuclear energy - Sethna, H. N., 1923- (Maharaja Sayajirao memorial lectures, 1980)
Transcript of lectures delivered by the Chairman, Atomic Energy Commission, Government of India.